“Greek Women as Sport Leaders - Masculine, Feminine or Androgenous Characteristics” - Πλακούδα, Αικατερίνη (Πανεπιστήμιο Πελοποννήσου, 2022)
The purpose of this dissertation is to explore the characteristics of women's leadership in sports management in addition to the leadership style they adopt and support. The systemic prejudices reported are behind the persistent failure to achieve gender equality in leadership roles. And since it is a complex systemic problem, its individual parts are also multifaceted and constantly evolving. The survey participants were 14 from the field of sports and leadership and the results of the research concern the 14 individuals of the sample and not the general population. They were all Greeks and they took part to the survey via internet due to the pandemic Covid-19. Although the subject of the study was women, the study was comparative and the participants were also men in order to create a more complete view on the subject. The mixed method was utilised for the present study. The mixed method is put for a certain purpose in both quantitative (questionnaire) and qualitative methods (interviews). Based on the answers of the participants of the MLQ - 5x short and after processing them in order to see based on percentages which leadership model stands out, it was concluded that the participants tend to the Laissez-faire leadership style with a percentage of 88,45%. Based on the answers of the participants of the BSRI and after processing them in order to see based on percentages which characteristic stands out, it was concluded that the averages of masculinity and femininity for both sexes are 51.54 and 40.90 respectively. Also, for the androgyny scale the average is 52.70. This characteristic seems to prevail, suggesting that women today have more masculine elements, while men retain the characteristics they traditionally had. In conclusion it was clear from the interviews that we need more women leaders in general and in the field of sports and its management in particular.
Ελληνίδες γυναίκες ως ηγέτιδες στον αθλητικό χώρο - αρσενικά, θηλυκά ή ανδρόγυνα χαρακτηριστικά
Keywords: Ηγεσία στις γυναίκες; Αθλητισμός - Διοίκηση και οργάνωση; Γυναίκες - Απασχόληση; Γυναίκες στελέχη επιχειρήσεων; Γυναίκες εργαζόμενες; Leadership in women; Sports - Management; Women - Employment; Women executives; Women employees; Greek Women; Women's Leadership; Characteristics